A novel ladder-like lectin relates to sites of mucosal immunity in Atlantic halibut (Hippoglossus hippoglossus L.). Issue 87 (April 2019) - Magnadottir, Bergljot; Gudmundsdottir, Sigridur; Lange, Sigrun
Abstract: A novel 27 kDa ladder-lectin-like protein, showing a multimeric structure under non-reducing conditions, was isolated from halibut serum by binding to N-acetyl glucosamine. Mass-spectrometry analysis did not show significant homology with known proteins. Specific antibodies were produced and used in immunohistochemistry on tissue sections of early halibut ontogeny from 119 until 1050 °d post hatching. A strong positive response was detected in the mucosal cells of the skin, gills and gut, indicating a role in the mucosal immune defence at these sites. Further immunopositivity was detected in liver, myeloma of kidney and the brain at different developmental stages but predominant expression was found in mucosal surfaces at later stages of development tested (1050 °d). It is still uncertain whether this ladder-like lectin forms part of the complement pathway, as a lectin or ficolin, or if it belongs to galectins. A strong detection in mucosal surfaces on skin, gills and gut, show similar patterns of expression as both mucosal lectins and galectins in other fish. Detection in neuronal tissue may indicate putative roles in tissue remodelling of brain and in ongoing neurogenesis in the fish eye. Highlights: A novel 27 kDa ladder-like lectin protein was isolated from halibut serum by binding to N-acetyl glucosamine (GlcNAc). The GlcNAc-binding halibut protein showed a multimeric ladder-like structure under non-reducing conditions. The GlcNAc-binding protein was detected in mucosal surfaces of skin, gills and gut and in liver and kidney in halibut ontogeny. Ontogeny detection in neuronal tissue of brain and eye indicates roles in tissue remodelling and neurogenesis.